Hyperbaric oxygen preconditioning for prevention of acute high-altitude diseases: Fact or fiction? - You, Jiuhong; Chen, Xinxin; Zhou, Mei; Ma, Hui; Liu, Qiaoling; Huang, Cheng (Frontiers in Physiology, 2023)
Acute high-altitude diseases, including acute mountain sickness (AMS), high-altitude cerebral edema (HACE), and high-altitude pulmonary edema (HAPE), have been recognized as potentially lethal diseases for altitude climbers. Various pre-conditioning stimuli, including hyperbaric oxygen (HBO), have been proposed to prevent acute high-altitude diseases. Herein, we reviewed whether and how HBO pre-conditioning could affect high-altitude diseases and summarized the results of current trials. Evidence suggests that HBO-preconditioning may be a safe and effective preventive method for acute high-altitude diseases. The proposed mechanism of HBO pre-conditioning in preventing high-altitude diseases may involve the following: (1) it protects the blood-brain barrier and prevents brain edema, (2) it inhibits inflammatory responsiveness, (3) it induces hypoxia-inducible factor and its target genes, and (4) it increases antioxidant activity. However, the optimal protocol of HBO pre-conditioning needs further exploration. Translating the beneficial effects of HBO pre-conditioning into current practice requires the “conditioning strategies” approach. More large-scale and high-quality randomized controlled studies are required for further exploration.